Forensic Outpatient Variables That May Help to Prevent Further Detention - Klinger, Karoline; Ross, Thomas; Bulla, Jan (Frontiers in Psychiatry, 2020)
Forensic outpatient treatment in Germany helps forensic patients back into society while managing the risk that these individuals present to public safety. Measures used to achieve this objective include psychiatric treatment, case management, and the treatment of risk factors that may cause criminal behavior. In addition to the effects of treatment and control, good living conditions have been hypothesized to help prevent criminal recidivism. Several studies have examined how living conditions affect recidivism among former prison inmates and how quality-of-life measures affect relapse rates in sexual offenders, but there is little research on the effects of living conditions on outcomes of forensic outpatients. In order to test the hypothesis that good living conditions reduce the risk of unfavorable outcomes such as criminal recidivism and subsequent confinement, we analyzed data from a forensic outpatient data project run by the federal state of Baden-Württemberg (Ambulanz-FoDoBa). Information on the patients’ working, living, and financial situation as well as information on their social situation and relationship status, was used as indicators for good living conditions. Based on data collected in six forensic treatment units throughout the federal state of Baden-Württemberg since 2015, we compared 61 forensic outpatients that had either regularly ended treatment (group one), or were referred back to a forensic hospital or prison (group two). The predictive validity of these factors on the treatment outcome was tested with a logistic regression model. There were a number of a priori differences between the groups, but assisted living in an outpatient environment was the only significant predictor of positive vs. negative outcome. Implications of the findings are discussed.